1992
DOI: 10.1017/s0033291700032797
|View full text |Cite
|
Sign up to set email alerts
|

The International Pilot Study of Schizophrenia: five-year follow-up findings

Abstract: SYNOPSIS A five-year follow-up of the patients initially included in the International Pilot Study of Schizophrenia was conducted in eight of the nine centres. Adequate information was obtained for 807 patients, representing 76% of the initial cohort. Clinical and social outcomes were significantly better for patients in Agra and Ibadan than for those in the centres in developed countries. In Cali, only social outcome was significantly better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(63 citation statements)
references
References 15 publications
6
52
0
5
Order By: Relevance
“…Comparative studies have actually demonstrated better long-term outcomes for schizophrenia in LMIC, particularly for individuals living in rural areas (Leff, Sartorius, Jablensky, Korten, & Ernberg, 1992). In one included study, authors point to the finding that people in Asian, African and Latin American countries tend to live with their extended families whereby family involvement in care may be more important than in Western cultures (Guo et al, 2010).…”
Section: Overall Intervention Findingsmentioning
confidence: 99%
“…Comparative studies have actually demonstrated better long-term outcomes for schizophrenia in LMIC, particularly for individuals living in rural areas (Leff, Sartorius, Jablensky, Korten, & Ernberg, 1992). In one included study, authors point to the finding that people in Asian, African and Latin American countries tend to live with their extended families whereby family involvement in care may be more important than in Western cultures (Guo et al, 2010).…”
Section: Overall Intervention Findingsmentioning
confidence: 99%
“…The follow-up study of patients diagnosed with schizophrenia in the International Pilot Study of Schizophrenia (IPSS) showed that, in spite of clinical similarity, there were remarkable variations in course and outcome within and across different cultures and those in developing countries including Agra (India) had a better outcome than those in developed countries (Leff et al 1992 ). Other studies, Determinants of Outcome of Severe Mental Disorders (DOSMeD), Madras Longitudinal study, and Study of Factors Associated with the Course and Outcome of Schizophrenia (SOFACOS), also observed the outcome to be more favorable in India (Craig et al 1997 ;Thara et al 2004 ;Verghese et al 1989 ).…”
Section: Culture and Schizophrenia In Indiamentioning
confidence: 99%
“…The IPSS found that four symptoms, auditory hallucinations, delusions, social withdrawal, and fl at affect, were common to all cultures (Leff et al 1992 ). The DOSMeD study found that the symptom profi le of patients was quite similar in developing and developed centers, apart from visual hallucinations being more frequent in the former and affective symptoms (mainly depression) in the latter (Craig et al 1997 ).…”
Section: Culture and Schizophrenia In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque veamos estos hallazgos como novedosos, recuerdan la hipótesis que postulaba que la mejoría en la conducta y síntomas psicóticos era proporcional al daño cerebral que producían, lo que se apo yaba con estudios de imagen 54 . Todo esto puede explicar los peores resultados en al gunas áreas relacionadas con la recupera ción de una vida productiva de los pacien tes que toman tratamiento de forma indefinida frente a los que no 55 , apoyando los hallazgos de los estudios de la OMS que encuentran mejores resultados en países en los que los pacientes no disponen de estos tratamientos 56 .…”
Section: Iatrogenia Del Tratamiento Psicofar Macológicounclassified